Perpaduan Isometric Exercise dan Latihan Pernafasan Yoga Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi di Desa Mojojajar Wilayah Kerja Puskesmas Kedungsari Kabupaten Mojokerto - Anjarsari, Dinda Risma Putri; Hanan, Abdul; Widiani, Esti (Faculty of Medicine, Universitas Andalas, 2021)
One of the non-pharmacological treatments that can be done to lower blood pressure is to increase the patient's physical activity, such as Isometric Exercise and Yoga breathing exercises. Objectives: To determined isometric exercise and yoga breathing on reducing blood pressure in hypertension. Methods: This study used a pre-experimental design with a one-group pretest-postest design. The sampling technique was purposive sampling. The number of samples in this study was 25 people. Results: The paired t-test statistical test results were a decrease in blood pressure after being given the intervention of isometric exercise and yoga breathing exercises with a p-value of 0.000 (p<0.05). Conclusion: Isometric exercise and yoga breathing exercises can be an alternative non-pharmacological therapy to reduce blood pressure in hypertension.Keywords: Â Isometric Exercise, Yoga Breathing Exercise, Hypertension